The Machiavellian cosmos - Parel, Anthony (Yale University Press, 1992)
In this highly original interpretation of Machiavelli's thought, Anthony J. Parel identifies a theme generally neglected in the scholarship on this sixteenth-century political thinker: Machiavelli's belief in the occult forces of heaven and humours. Challenging the current tendency to view Machiavelli as a pioneer of modern political science, Parel argues instead that a premodern cosmology and anthropology underlie Machiavelli's political works. Parel shows that Machiavelli's world picture owes more to the astrological cosmology prevalent in the Renaissance than to the Aristotelian or Platonic or Christian world picture. This astrological determination significantly affects. Machiavelli's conceptions of history, politics and religion and shapes his notions of virtu and fortuna. It also has considerable impact on his ethical ideas: the Machiavellian cosmos has no room for a Ruling Mind or for the Sovereignty of the Good, and humans are left to pursue their appetites for riches and glory as best they can. In a similar fashion, says Parel, Machiavelli's political anthropology is influenced by the ancient idea that body humours determine a person's temperament and behaviour, for he believes that humours compromise human autonomy and rationality. The theory of humours also affects Machiavelli's view of the body politic and his characterization of republics, princedoms and licenzia, and Parel explicates this in his new readings of The Prince, the Discourses and the Florentine Histories.